Biosynthesis of selenium nanoparticles of Monascus purpureus and their inhibition to Alicyclobacillus acidoterrestris. (December 2021) - Sun, Yuhan; Shi, Yiheng; Jia, Hang; Ding, Hao; Yue, Tianli; Yuan, Yahong
Abstract: Alicyclobacillus acidoterrestris is a kind of acid-resistant and heat-resistant gram-positive bacteria which can produce undesirable odors, causing fruit juice spoilage. However, conventional industrial sterilization methods cannot kill this bacterium. Antimicrobial nanoparticles could serve as promising antibacterial agents to inhibit A. acidoterrestris . In this work, selenium nanoparticles (SeNPs) were produced in the fermentation process of a selenium-enriched strain Monascus purpureus 2322 which domesticated in laboratory and their antibacterial activity against A. acidoterrestris was investigated. The as synthesized SeNPs was around spherical with a diameter of approximately 48 nm. Moreover, SeNPs could severely damage the integrity of bacterial cell, resulting in the leakage of cellular contents. Therefore, A. acidoterrestris was inhibited in the presence of SeNPs. These results indicate that the generation of SeNPs by fermentation provides a new efficacious way for developing antibacterial agent against A. acidoterrestris . Graphical abstract: Image 1 Highlights: The selenium nanoparticles produced by Monascus purpureus was obtained for the first time. The selenium nanoparticles produced by M. purpureus was systematically characterized for the first time. It is the first time to verify the inhibitory effect of selenium nanoparticles on Alicyclobacillus acidoterrestris. The fundamental mechanism of inhibition of A. acidoterrestris by selenium nanoparticles was described for the first time.